PERAN KOMPENSASI FINANSIAL DAN NON FINANSIAL DALAM MENINGKATKAN RETENSI KARYAWAN - Fathya Jihan Natasya; Nafiah Ilhamah Qurratu'aini; Rizal Idul Fitrianto (Fakultas Ekonomi Universitas Islam Darul Ulum Lamongan, 2025)
Compensation, both financial and non-financial, plays a crucial role in enhancing employee retention. Financial compensation such as competitive salaries, bonuses, and performance-based incentives provide rewards for employees' contributions and create a sense of fairness, which is essential for attracting and retaining talent within the company. Meanwhile, non-financial compensation such as recognition, career development opportunities, work flexibility, and a supportive work environment plays a vital role in building strong emotional bonds between employees and the company, which in turn enhances their loyalty and motivation. Both types of compensation affect satisfaction, loyalty, and employee turnover rates. The implementation of transparent, fair, and relevant compensation policies can reduce turnover and foster a positive work climate. A good policy also helps improve the relationship between management and employees and supports the achievement of the company's long-term strategic goals. By designing an effective compensation system, companies can ensure organizational sustainability and success through increased employee retention, who are committed and motivated to contribute optimally.